2019
DOI: 10.3390/metabo9100231
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolomics Unravel the Effect of Magnesium Oversupply on Tomato Fruit Quality and Associated Plant Metabolism

Abstract: In general, greenhouse cultivation involves the rampant application of chemical fertilizers, with the aim of achieving high yields. Oversaturation with mineral nutrients that aid plant growth, development, and yield may lead to abiotic stress conditions. We explore the effects of excess magnesium on tomato plant metabolism, as well as tomato fruit quality using non-targeted mass spectrometry (MS)-based metabolomic approaches. Tomato plants were subjected to three different experiments, including high magnesium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 39 publications
2
34
1
Order By: Relevance
“…In summary, we examined the effects of nutrient and water supply on metabolic changes in tomato fruits cultivated in soil with excess Mg 2+ under greenhouse conditions. As the growth, metabolites, and fruit quality of tomato plants under excess Mg 2+ soil were affected differently than plants in soils without excess Mg 2+ in Kwon et al (2019), the effects of nutrient and water were contrary to previous results. Our results suggest that the lowest nitrogen coupled with sufficient water supply condition enhanced the lycopene content of tomato fruits on a dry-weight basis, and that limiting water supply in any nutrient supply condition was not appropriate to enhance sugars and organic acids under greenhouse cultivation when soil had excess Mg 2+ .…”
Section: Resultscontrasting
confidence: 94%
See 1 more Smart Citation
“…In summary, we examined the effects of nutrient and water supply on metabolic changes in tomato fruits cultivated in soil with excess Mg 2+ under greenhouse conditions. As the growth, metabolites, and fruit quality of tomato plants under excess Mg 2+ soil were affected differently than plants in soils without excess Mg 2+ in Kwon et al (2019), the effects of nutrient and water were contrary to previous results. Our results suggest that the lowest nitrogen coupled with sufficient water supply condition enhanced the lycopene content of tomato fruits on a dry-weight basis, and that limiting water supply in any nutrient supply condition was not appropriate to enhance sugars and organic acids under greenhouse cultivation when soil had excess Mg 2+ .…”
Section: Resultscontrasting
confidence: 94%
“…Saline drainage water containing not only high Na + but also high Mg 2+ has been used to cultivate tomatoes in the field (Mitchell et al, 1991). Recently, the effects of Mg oversupply on the metabolite content of tomato plants and fruits were extensively investigated by Kwon et al and they reported poor fruit quality under excess Mg conditions (Kwon et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The MS data were collected in the range of 100–1500 m/z (under negative- and positive-ion modes) using an Orbitrap Velos Pro ™ system, which was combined with an ion-trap mass spectrometer (Thermo Fisher Scientific) coupled with a HESI-II probe. The samples were analyzed following the protocols described by Kwon et al [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Total soluble sugars were assessed using the colorimetric anthrone method (Huang et al, 2017). TA and soluble protein concentrations were determined as described in Kwon et al (2019) and Wang et al (2016), respectively. The precipitation obtained when extracting sugars was autoclaved for 1 h and then incubated with amyloglucosidase in 12 mL acetate buffer (0.25M, pH4.5, 55 C) for a 1 h. The sample was then centrifuged for 10 min at 7,000 rpm.…”
Section: Total Soluble Sugars Ta Soluble Protein Starch and Vitamimentioning
confidence: 99%